Friedrich Engels and Feminist Jurisprudence: one step back, two steps forward - ALMEIDA, Miguel Régio de (Revista Jurídica Portucalense, 2023)
In a purely pedagogical and non-exhaustive approach, I recall the theoretical contribution of a thinker who is essential for anyone interested in the link between Law and Feminism. Focusing on the epistemological aspect of such connection, I argue about the pertinence of evoking some of Friedrich Engels’ literary works. Namely, The Origin of the Family, Private Property and the State (1884), where he innovatively exposed many of the lines along which patriarchy structures and exercises female oppression, supported by legal normativity. As these reflections are set within the larger context of the capitalist economic model, Engelsian cogitations have shown themselves to be continuously current and transversal to the “streams” of liberal, cultural, radical, post-modern, post-colonial and anti-capitalist feminism. If no jurist – namely those who consider themselves aware of the gender inequality innate to the androcentric world of legality – should ignore the contributions of this precursor of Critical Legal Studies, the challenge takes on special weight within Lusitanian legal thought. Given its historically conservative genealogy and modus vivendi, not only have CLS in general reaped little reception, but the specificities of Feminist Jurisprudence do not yet have the urgent projection they deserve. Let a step back, following the insights of Friedrich Engels, be a stimulus to move two steps forward, overcoming the juridical backwardness that still tarnishes Portuguese society.